Learned Helplessness as a Mediating Variable between the Attributional Style and Academic Achievement - Ciżkowicz, Barbara (Przegląd Badań Edukacyjnych (Educational Studies Review), 2017)
Theories and empirical studies link attributional style with many areas of everyday life including academic performance. Attributional style is also a theoretical construct important in explaining the motivation of achievement and development of learned helplessness. The present study was conducted on a sample of 328 undergraduate students. This study examines the relationship between the attributional style and academic performance, taking into account the role of helplessness as mediator and moderating role of gender. The Attributional Style Questionnaire (ASQ; Peterson et al., 1982) was used to measure the attributional style. The anxiety and happiness were used as criterial variables in assessing the relevance of ASQ. The assessment of their psychometric properties allowed to choose the aggregation level with satisfactory reliability (α>0,70) and validity. Attributional style shows a weak (failure β = 0.21; successful β = -0.13) but significant relationship with achievement in science. The introduction of learned helplessness, as an mediating variable revealed a significant effect of suppression (failure β = 0.28; successful β = -0.21), and inclusion of gender as a moderator significantly improves the predictive ability of the models (Δ R2 respectively 12.9% and 24,1% of the variance of average grade). In each regression model the direct effect of the attributional style on average grade shows that the higher optimism in the interpretation of events, the lower the grades.